Benefits of electroacupuncture and a swimming association when compared with isolated protocols in an osteoarthritis model - Gustavo Andrade Martins; Andressa Nayara Degen; Flavia Tasmin Techera Antunes; Luiza Gabriela da Rosa; Alice Gomez Ferraz; Elenir Wiilland; Luciene Bruno Vieira; Alessandra Hubner de Souza (Journal of Traditional and Complementary Medicine, 2022)
Background and aim: Osteoarthritis (OA) is characterized by pain and inflammation. Electroacupuncture (EA) and swimming (SW) are non-pharmacological interventions recommended for treating OA. The study evaluated the benefits of electroacupuncture (EA) and swimming (SW) association when compared with isolated protocols in an OA rodent model. Experimental. Procedures: An ankle monoarthritis model was induced in rats by applying Complete Freund's Adjuvant (CFA). After seven days of induced OA, the groups were submitted to EA (ST36 and the GB 30 Acupoint), SW, or the EA + SW protocol. The nociceptive behavior was measured by the Von Frey test, the Cold Stimulation test, and the Paw Flick Immersion test. Inflammatory activity was evaluated by measuring TNF levels, myeloperoxidase, NAGase, immunological parameters and the histology from the subcutaneous tissue. Results: Compared to CFA group, EA decreased the nociceptive scores in the cold stimulation test (p < 0.05), and it also increased the latency time in thermal cold (p < 0.01) and heat hyperalgesia (p < 0.001). Also, EA reduced NAGase (p < 0.01). SW reduced the edema (p < 0.05) and did not increase the inflammatory infiltrates or congestion, neither in the histological measurements nor by analyzing the levels of TNF. The association of EA + SW decreased the neutrophils and the monocytes, MPO (p < 0.05), and the glutamate levels in the cerebrospinal fluid (CSF, p < 0.001). Conclusion: There were statistical differences between combination therapy and monotherapy as seen by the inflammatory parameters, which could be associate to the delay of the chronification osteoarthritis retardation. However, EA + SW did not show benefits when compared to isolated protocols in nociceptive behavior.